Re-Design Struktur Gedung Head Office Awann Group Berdasarkan Integrasi BIM Autodesk melalui Revit, Naviswork, dan SAP2000 - Adam Rizky Christiandava; Adelia Azzahra; Asri Nurdiana; Bambang Setiabudi (Jurnal Sipil dan Arsitektur, 2023)
Building Information Modeling (BIM), implementation is an innovative advancement in the construction industry. Generally, developing a construction project requires several phases in which information is created manually using a lot of software. Unfortunately, the steps that must be completed in conventional software for project management are inefficient and susceptible to misinterpretation, which frequently causes issues. Therefore, this study focuses on re-planning the Awann Group Semarang Head Office Building using BIM integration based on Autodesk Revit, Naviswork, and SAP 2000 planning software. Re-planning is conducted under SNI 2847-2019 for structural concrete planning requirements, SNI 1727-2020 for minimum load review, and SNI 1726-2019 for structural earthquake resistance standards. This plan produces structural analysis for calculating the feasibility of a building structure, 3D designs from Revit software that can generate 2D designs for Detail Engineering Designs, and work volumes for RAB calculations. Then, for scheduling, Revit will be integrated with Naviswork, which can display scheduling with 3D visualization. The re-planning of the Head office of the Awan Group Semarang resulted in a budget plan of Rp. 4,661,246,792.98 was calculated using the automatic Quantity Take Off from Autodesk Revit and scheduling planning using Microsoft Project and Autodesk Naviswork for ten months of work.